Health impact of catch‐up growth in low‐birth weight infants: systematic review, evidence appraisal, and meta‐analysis. Issue 1 (22nd March 2016) - Martin, Anne; Connelly, Andrew; Bland, Ruth M; Reilly, John J
Abstract: This study aimed to systematically review and appraise evidence on the short‐term (e.g. morbidity, mortality) and long‐term (obesity and non‐communicable diseases, NCDs) health consequences of catch‐up growth (vs. no catch‐up growth) in individuals with a history of low birth weight (LBW).We searched MEDLINE, EMBASE, Global Health, CINAHL plus, Cochrane Library, ProQuest Dissertations and Thesis and reference lists. Study quality was assessed using the risk of bias assessment tool from the Agency for Health Care Research and Quality, and the evidence base was assessed using the GRADE tool. Eight studies in seven cohorts (two from high‐income countries, five from low‐middle‐income countries) met the inclusion criteria for short‐term (mean age: 13.4 months) and/or longer‐term (mean age: 11.1 years) health outcomes of catch‐up growth, which had occurred by 24 or 59 months. Of five studies on short‐term health outcomes, three found positive associations between weight catch‐up growth and body mass and/or glucose metabolism; one suggested reduced risk of hospitalisation and mortality with catch‐up growth. Three studies on longer‐term health outcomes found catch‐up growth were associated with higher body mass, BMI or cholesterol. GRADE assessment suggested that evidence quantity and quality were low. Catch‐up growth following LBW may have benefits for the individual with LBW in the short term, and may have adverse population health impacts in the long‐term, but the evidence is limited. Future cohort studies could address the question of the consequences of catch‐up growth following LBW more convincingly, with a view to informing future prevention of obesity and NCDs. © 2016 John Wiley & Sons Ltd